Pengaruh Kebijakan Restriksi Pemberian Hibah Bansos terhadap Politisasi Anggaran oleh Calon Incumbent pada Pilkada Kabupaten/Kota Tahun 2017 - Mansyur, Abdul Rahman (Jurnal Kebijakan Ekonomi, 2022)
The purpose of this research is to analyze to what extent the restriction policy on grants and social assistance budget allocation may prevent political budget cycles (PBC) in the era of a regional election on regions that had incumbent candidates, by taking the case of the simultaneous regional election of 2017 in 94 regencies/cities in Indonesia. By utilizing fixed effect regression on panel data from 2014 through 2018, this research finds that there are no significant differences in the growth of grants and social assistance budget in the political years of 2016-2017 between regencies/cities that had incumbent candidates and those that did not. There are indications that the restriction policy that was implemented in 2016 is associated with the absence of political budget cycles (PBC) in the regions that had incumbent candidates.